Reconfigurable intelligent surface with high optical-transparency based on metalmesh - Jing Cheng Liang; Peng Zhang; Qiang Cheng; Tie Jun Cui (Journal of Information and Intelligence)
Reconfigurable intelligent surfaces (RISs) have aroused extensive attentions from academic and wireless communication communities due to their abilities to customize the electromagnetic (EM) characteristics of the propagation channels flexibly and rapidly. Recent advances in theoretical innovations and prototype systems have demonstrated the advantages of RISs in terms of low cost, low power consumption, and easy deployment. Meanwhile, the optically transparent RISs are demanded in some application scenarios. In this paper, we propose a 2-bit metalmesh-based RIS with high optical-transparency. By analyzing the surface current distributions on the element, we employ the metalmesh-grid patterns and metalmesh-stripe patterns on the top and ground layers respectively. The metalmesh patterns can help improve the optical transparency of RISs, while maintaining similar microwave characteristics. The RIS can reach the optical transparency of 79%, and the reflection amplitude is greater than −3.2 ​dB within the operating band. Finally, to verify the capability of the proposed RIS in wavefront controls, the far-field scattering patterns of the RIS with different coding sequences are investigated and the simulation results are in good agreement with the theoretical results.